Urgensi Keberadaan Otoritas Pengawasan Independen Terhadap Harmonisasi Hukum Perlindungan Data Pribadi Di Indonesia - Halbert, Giovanno; Rusdiana, Shelvi; Hutauruk, Rufinus Hotmaulana (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Personal data is one of the most crucial aspects in Indonesia, which has been following the digital development. Unlike Singapore and Japan, which already have institutions overseeing the protection of personal data, Indonesia does not have one yet and is still aspiring to establish an independent supervisory authority that can assist the public in personal data protection. This research employs a normative juridical study with a legal approach and a conceptual approach. The result of this research is the need for harmonization between Law Number 27 of 2022 on Personal Data Protection and Law Number 11 of 2008, as amended by Law No. 19 of 2016 on Electronic Information and Transactions, with the regulations of Singapore's Personal Data Protection Act and Japan's Act on the Protection of Personal Information as a comparative model to establish an independent institution regulating personal data in Indonesia.